(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
Teaching and Learning``meet’’ in the teaching and learning environment. Building a good learningenvironment means taking into account both the psychologist’s and theinstruction list’s perspectives. Many administrators and instructors arefamiliar with course management systems and campus portals, fewer haveexperience with virtual worlds and may question their academic relevance. Theteaching activities of the teacher and the learning activities of the learnerare both directed towards matching individual performances.